What are the main features of the dominant educational ideology espoused at Bethlehem College? : a thesis presented in partial fulfilment of the requirements for the degree of Master of Education in Education at Massey University - Giles, David (Massey University, 1995)
This case study is an inquiry into a Christian view of Education. More specifically, what is sought in this research, are the characteristics of the dominant educational ideology held within a private interdenominational Christian school. An educational ideology represents the ideas and beliefs held in common by the members of the school regarding the arrangements for schooling in their particular context. Although a number of different ideologies may co-exist, it is the dominant ideology that is being sought in this study. A framework for the articulation of ideologies, most recently developed by Brown (1988), will be used as the basis for the analysis of this school's educational ideology. In this framework, an ideology is analyzed through the identification of distinctive features within several component theories which constitute the overarching educational ideology. These component theories include the school's view of: knowledge, its content and structure; learning and the learners' role; teaching and the teachers' role; the organisation of the learning situation; and its aims, objectives and outcomes. The school used in this research is Bethlehem College in Tauranga New Zealand. Since its establishment in 1988, Bethlehem College has opened an Early Childhood Centre, Primary school, Secondary school and a Teachers College, presently catering for seven hundred students. Currently, it is developing plans towards greater involvement in adult education programmes, somewhat akin to Polytechnic and University courses. Moreover, the demand for student enrolments at Bethlehem College has had a waiting list in excess of four hundred students.
Keywords: New Zealand Tauranga District; Church schools; Bethlehem College